Avaliação da influência de anticoagulantes sobre parâmetros da validação de métodos bioanalíticos para estudos farmacocinéticos e de biodisponibilidade/bioequivalência de succinato de sumatriptano e naproxeno sódico - Juliana Machado Brêtas (2014)
HPLC-MS/MS is the technique of choice for drug and metabolites analysis in biological matrices, such as in bioavailability/bioequivalence or pharmacokinetics studies. The high levels of selectivity and sensitivity associated with this technique are largely affected by the occurrence of matrix effect in bioanalytical methods. Matrix effect results from co-eluting matrix components, such as anticoagulants used to obtain plasma, the main biological matrix employed in bioanalysis. The most commonly used anticoagulants in bioanalysis are heparin and EDTA and a sodium citrate, sodium phosphate, citric acid, dextrose and adenine solution (CPDA) or a citrate, phosphate, dextrose, saline, adenine, glucose and mannitol solution (CPD/SAG-M) are used for blood collection in bags. The combination of naproxen (NAP), a non-steroidal anti-inflammatory, and sumatriptan (SUM), a selective 5-hydroxytryptamine1B/1D receptor agonist, is used for the acute treatment of migraine. NAP is an acidic compound (pKa 4.8) and SUM is a basic compound (pKa 9.63), and this large difference in pH is the limiting factor in the development of procedures for sample preparation, chromatographic separation and detection. In this study we evaluated the impact of the type of anticoagulant (heparin, EDTA or CPDA), the counterion (sodium or potassium) and the ion concentration in the anticoagulant solution on the validation parameters and on the pharmacokinetic measures obtained in the analysis of samples from healthy volunteers in the simultaneous quantification of NAP sodium and SUM succinate in human plasma by HPLC-MS/MS with positive electrospray ionization (ESI (+)). For this purpose, a bioanalytical method was developed and validated according to the ANVISA Resolution RDC no. 27, 17 May 2012 in three different matrices: plasma containing heparin, EDTA or CPDA. After validation, the method was applied on volunteers samples that were collected in tubes containing heparin or EDTA. According to the results, there was no statistically significant difference between the analyzed plasmas containing each anticoagulant on any of the validation parameters and on any of the pharmacokinetic measures. Therefore, the type of anticoagulant, the associated ion and the ion concentration in the anticoagulant solution do not impact on the simultaneous quantification of NAP sodium and SUM succinate in human plasma by HPLC-MS/MS ionization ESI (+).